After She's Gone - Jackson, Lisa (Thorndike, Maine : Center Point Large Print, 2016)
"Sisters Cassie and Allie Kramer dream of fame, but while Cassie got only bit parts, the younger, more beautiful, and more talented Allie rose to stardom. When Allie's body double is shot on the movie set and Allie goes missing, Cassie becomes a suspect and is convince the only way to end her nightmare is to find Allie"--
Keywords: Large type books; Suspense fiction